풍력단지 발전량 예측에 대한 재해석 자료 ERA5의 현장적응 - 김진영(Kim Jin-Young); 황수진(Hwang Su-Jin); 김현구(Kim Hyun-Goo); 박채영(Park Chae-Young); 정준영(Jeong Jun-Young) (한국태양에너지학회 논문집, 2022)
Owing to the continuously improving spatial resolution and accuracy of the reanalysis data, a site adaptation case study was performed for the prediction of wind farm power output using ERA5, the 5th generation reanalysis data. The wind speed of the reanalysis data was substituted into the performance curve of the wind turbine by altitude and topographical speed up/down correction using the power law for maximizing the correlation between the predicted and actual power record. Cluster analysis was conducted to classify the wind farms into five groups, and representative onshore, inland, mountain wind farms were selected for case analysis from each cluster. Via the site adaptation of 41 wind farms in South Korea, the hourly, daily cumulative, and monthly cumulative correlation coefficients of the power output were calculated, which were 0.68, 0.79, and 0.85, respectively. In future, machine learning will be introduced for site adaptation in conjunction with the downscaling of wind resource maps by numerical weather prediction or computational fluid dynamics. KCI Citation Count: 0